The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fmicb.2022.958917
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of endophytic bacterial and fungal microbiota associated with the medicinal lichen Usnea longissima at high altitudes

Abstract: Endophytic microbial communities of lichen are emerging as novel microbial resources and for exploration of potential biotechnological applications. Here, we focused on a medicinal lichen Usnea longissima, and investigated its bacterial and fungal endophytes. Using PacBio 16S rRNA and ITS amplicon sequencing, we explored the diversity and composition of endophytic bacteria and fungi in U. longissima collected from Tibet at five altitudes ranging from 2,989 to 4,048 m. A total of 6 phyla, 12 classes, 44 genera,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Still, it is important to conduct culture-based studies, such as this. Isolates recovered from this study and from other similar studies [26,27,60] will allow us to thoroughly investigate the biology of these fungi. In addition to this, some endolichenic fungi can also be of biotechnological importance, such as oleaginous yeasts [24].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Still, it is important to conduct culture-based studies, such as this. Isolates recovered from this study and from other similar studies [26,27,60] will allow us to thoroughly investigate the biology of these fungi. In addition to this, some endolichenic fungi can also be of biotechnological importance, such as oleaginous yeasts [24].…”
Section: Discussionmentioning
confidence: 89%
“…Globally, studies involving endolichenic fungi led to the identification and discovery of various new and previously identified fungal taxa representing various lineages of Ascomycota, such as Pezizomycetes, Dothideomycetes, Eurotiomycetes, Leotiomycetes, and Sordariomycetes, among others [20][21][22][23]. Echoing the global trend, several novel endolichenic fungal taxa were also identified in China [24][25][26][27][28]. In a recent fungal biodiversity study by Xu et al (2022), the authors detected a substantial diversity of endolichenic fungi in the family Teratosphaeriaceae from Heterodermia obscurata, and proposed that Teratosphaeriaceae is likely to be one of the core endophytic fungal families associated with this lichen [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we could show that the alpha diversity of bacteria decreased from soil toward lichen samples (Figure 1A ), but because there is no description work about alpha diversity on lichen growth different partition, we can't compare our results with existing lichen literature. What the slightly related studies reported the lichen bacterial community structure at different growth stages, geographical flora, and growth substrates, and so forth [ 20 , 34 , 35 , 36 ]. Although the bacterial microbiota is considered of importance for the holobiome, there have so far only been microscopic observations of differences between upper and lower surfaces of lichens [ 12 ].…”
Section: Discussionmentioning
confidence: 99%